Interaction design in an advertising agency. Analysis and improvement - Mato Lopez, Jonatan (My University, 2013)
The advertising industry has evolved considerably during the history, going from simple drawings on a rock to the use of digital channels we have nowadays. With this evolution, its professionals have been forced to adapt to new methodologies, strategies and ways of working, in order to take full advantage of the evolving technologies and systems. However, the adaptation is not always as easy, fast and smooth as one would want it to be, since a great amount of new concepts and ideas must be understood before one can fully apply a new approach to an activity that has been performed for some time. Nowadays, with digital channels such as websites or apps, a gigantic change has occurred: from consuming advertisement to use it. Therefore, a new approach to its design is necessary in order to increase the success of the results, the approach Interaction design offers. Interaction design provides a set of methodologies and ideas focused on the design of the use, the experience, with a closer relationship and attention to the future users. However, despite the big synergy this field has with the new paradigm digital interactive content design offers, many have failed to start this relationship, due to either a lack of knowledge of the field itself, or about how to apply it successfully. With this master thesis I intend to provide a clear and detailed set of methods, which make up an improved design process for digital interactive content within the advertising industry. In order to do this, I studied how these companies work and which are their specific needs. The results from this thesis are useful for any advertising company, but especially for those having troubles adapting to the new paradigm digital channels introduce to their activities. However, and secondarily, other professionals such as smaller companies or freelance designers can find use to the resulting design process, since their way of working would benefit from the knowledge the leading advertising agencies have gathered through their experiences during the years.
Keywords: Informations- och kommunikationsteknik; Interaktionsteknik; Information & Communication Technology; Interaction Technologies